Luciérnagas de la memoria. Altares espontáneos y narrativas de luto en Medellín, Colombia (2015)
ABSTARCT: Our objective is to analyze the cultural actions and practices subjects use to reconstruct their memories in contexts of violence, and identify the political use of their memory as political resistance in spaces for the daily, the intimate, the familiar or the communitarian. This work is a qualitative research which used case studies because of its focus on this matter and because it addresses the significance of an experience based on systematic analysis of the same phenomenon. The techniques used to collect data were bibliographic and documentary research and in-depth interviews. We identified four experiences creating spontaneous altars in the city of Medellin, Colombia, which were a mural listing dead people, a graffiti paying homage to two dead female students, an altar to the Virgin to remember the victims of a massacre and a Calvary to bury the dead remains of a murdered son. We opted for micro-stories to comprehend the political sense of returning to everyday matters after facing violent situations. The spontaneous altars are mourning rituals in a public space created as a reply to deaths they deemed unjust. They are forms of non-institutional political actions whose aim is to highlight what happened, express people’s indignation and avoid recurrence. In the cases studied, we confirmed that in the creation of altars, they expressed a narrative of mourning which demands for the recognition of their loss.